A Novel Strategy of Combined Pulsed Electro-Oxidation and Electrolysis for Degradation of Sulfadiazine - Dong Ma; Bo Zhang; Xiaomin Hu (Molecules, 2023)
A combination of the peroxymonosulfate (PMS) electro-activation process and the electro-oxidation process driven by a pulsed electric field (PEF) was used to degrade sulfadiazine (SND) wastewater. Mass transfer is the limiting step of electrochemical processes. The PEF could enhance mass transfer efficiency by reducing the polarization effect and increasing the instantaneous limiting current compared with the constant electric field (CEF), which could benefit the electro-generation of active radicals. The degradation rate of SND after 2 h was 73.08%. The experiments investigated the effects of operating parameters of pulsed power supply, PMS dosage, pH value and electrode inter distance on the degradation rate of SND. The predicted response value of single-factor performance experiments was obtained as 72.26% after 2 h, which was basically consistent with the experimental value. According to the quenching experiments and EPR tests, both SO4•− and •OH were present in the electrochemical processes. The generation of active species were significantly greater in the PEF system than that in the CEF system. Moreover, four kinds of intermediate products were detected during the degradation by LC-MS. This paper presents a new aspect for electrochemical degradation of sulfonamide antibiotics.